2009
DOI: 10.1002/jrs.2357
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy as a potential method for the detection of extremely halophilic archaea embedded in halite in terrestrial and possibly extraterrestrial samples

Abstract: Evidence for the widespread occurrence of extraterrestrial halite, particularly on Mars, has led to speculations on the possibility of halophilic microbial forms of life; these ideas have been strengthened by reports of viable haloarchaea from sediments of geological age (millions of years). Raman spectroscopy, being a sensitive detection method for future astrobiological investigations onsite, has been used in the current study for the detection of nine different extremely halophilic archaeal strains which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 66 publications
1
51
0
6
Order By: Relevance
“…Two laser excitation wavelengths were used: nonresonant 1,064 nm and resonant 514.5 nm. The main peaks collected (1,507, 1,152, and 1,002 cm Ϫ1 ) could be mainly assigned to bacterioruberin (95).…”
Section: Raman Features Of Pigments From Natural Biogeological Samplesmentioning
confidence: 93%
“…Two laser excitation wavelengths were used: nonresonant 1,064 nm and resonant 514.5 nm. The main peaks collected (1,507, 1,152, and 1,002 cm Ϫ1 ) could be mainly assigned to bacterioruberin (95).…”
Section: Raman Features Of Pigments From Natural Biogeological Samplesmentioning
confidence: 93%
“…It has already been demonstrated that benchtop instrumentation is able to detect biomolecules associated with extremophilic colonization of rocks (Russell et al, 1998;Edwards, 2000a, 2000b;Edwards et al, 2005;Villar et al, 2005;Marshall et al, 2006;Fendrihan et al, 2009), which provide model terrestrial organisms as analogues for those that may have been present on Mars. A specially constructed miniaturized Raman system, however, is an essential requirement for implementation of these in situ robotic measurements on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…In another case of salinixanthin from S. ruber Raman spectra indicate that there are few structural differences [52]. Other studies also demonstrated in laboratory conditions that benchtop instrumentation is able to detect biomolecules associated with the extremophilic endolithic colonization of rocks [38,[53][54][55][56][57][58][59][60].…”
mentioning
confidence: 96%